Mortality and associated factors among adult patients on tuberculosis treatment in Tanzania: A retrospective cohort study. (August 2021) - Bukundi, Elias M.; Mhimbira, Francis; Kishimba, Rogath; Kondo, Zuweina; Moshiro, Candida
Highlights: The crude mortality rate was estimated at 6.31 per 1000 person-months (pm). More than half of deaths occurred in the first two months of treatment. Lower survival probabilities were observed among TB/HIV co-infected, older TB patients, and retreatment TB patients. Abstract: Introduction: Tuberculosis (TB) is the global leading cause of death from an infectious agent. Tanzania is among the 30 high TB burden countries with a mortality rate of 47 per 100, 000 population and a case fatality of 4%. This study assessed mortality rate, survival probabilities, and factors associated with death among adult TB patients on TB treatment in Tanzania. Methods: A retrospective cohort study was conducted utilizing case-based national TB program data of adult (≥15 years) TB cases enrolled on TB treatment from January 2017 to December 2017. We determined survival probabilities using the Kaplan-Meier estimator and a Cox proportional hazard model was used to identify independent risk factors of TB mortality. Hazard ratios and their respective 95% confidence intervals were reported. Results: Of 53, 753 adult TB patients, 1927 (3.6%) died during TB treatment and the crude mortality rate was 6.31 per 1000 person-months. Male accounted for 33, 297 (61.9%) of the study population and the median (interquartile range [IQR]) age was 40 (30–53) years. More than half 1027 (56.7%) of deaths occurred in first two months of treatment. Overall survival probabilities were 96%, and 92% at 6th and 12th month respectively. The independent risk factors for TB mortality among TB patients included: advanced age ≥ 45 years (adjusted hazard ratio (aHR) = 1.74, 95% confidence interval (CI) = 1.45–2.08); receiving service at the hospital level (aHR = 1.22, 95% CI = 1.09–1.36); TB/HIV co-infection (aHR = 2.51, 95% CI = 2.26–2.79); facility-based direct observed therapy (DOT) option (aHR = 2.23, 95% CI = 1.95–2.72); having bacteriological unconfirmed TB results (aHR = 1.58, 95% CI = 1.42–1.76); and other referral type (aHR = 1.44, 95% CI = 1.16–1.78). Conclusion: Advanced age, TB/HIV co-infection, bacteriological unconfirmed TB results, other referral types, receiving service at facility-based DOT option and obtaining service at the hospital level were significant contributors to TB death in Tanzania. Appropriate targeted intervention to improve TB referral systems, improve diagnostic capacity in the primary health facilities, minimize delay and misdiagnosis of TB patients might reduce TB mortality.